The Effect of Career Development in the Millennial Generation - Triana, Ika; Prihandoko, Danang (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2024)
This study explains employee engagement for millennial employees. It identifies a career development that supports millennial employees, particularly in the DKI Jakarta area, to achieve better employee engagement, and the phenomenon of job-hopping reduces generation millennials. The subject of the investigation is employees of the millennial generation in the DKI Jakarta, with 407 questionnaire participants. The primary data of this study were obtained from questionnaires completed by several respondents. In addition, the data is processed using path analysis to analyze the relationship pattern between variables. This research uses a cross-sectional design. Data are collected only at one point in time, making it difficult to assess long-term causal relationships. Results showed that career development has a positive impact on employee engagement. Companies need to develop professional development programs tailored to the aspirations and work styles of this generation to increase effectiveness. Future longitudinal research may provide further insight into changing dynamics over time. Data collected via questionnaires may contain respondent bias due to their self-reported nature. Additional data collection methods, such as interviews or observations, may help reduce this bias. This research sheds light on the job-hopping phenomenon among millennial employees in Jakarta, the economic and business center of Indonesia. It makes a special contribution to the limited literature on the work behavior of millennials in major Southeast Asian cities. This research provides new insights into how career development and employee engagement can work together to reduce job hopping, thereby providing additional value to companies seeking to retain their employees